Marketing Strategy Analysis To Increase Layer Purebred Chiken Sales (Case Study UD Prapta,PesedahanVilage, Manggis Sub-District, Karangasem Regency - N. K. M. S, Astrini; Cakra, G. L. O.; Suryani, N. N. (Jurnal Peternakan Tropika, 2019)
This student work practice aims to determine the internal and external factors that influence the marketing of layer purebred chicken and analyze the appropriate alternative strategies applied at UD Prapta.This activity was held for one month (November 2018) involving 50 respondents consisting of 15 layer purebred chicken farmers, 30 consumers and 5 experts.Respondents of farmers are determined by random sampling method, consumer respondents are determined by random sampling, and expert respondents are determined by purposive sampling.Data collection is done by direct observation in the field by conducting interviews, and filling out questionnaires.Analysis used in this study is EFE-EFI, IE Matrix, and SWOT Matrix.The results of the IFE-EFE analysis show that the value of internal factors is 2.39 and the external factor value of 2.83 which shows the business position of UD Prapta is in quadrant V in the IE matrix that is division of preserving and maintaining. There are four alternative strategies that are produced, they are1) held a socialization regarding to the era of industry revolution 4.0; 2) applying the use of applications that can help the marketing process;3) socialization of marketing management;4) Build cooperation with parties who need eggs in large capacity and make a sale and purchase agreement. Keywords: layer purebred chicken, survey, marketing strategies, IE